A NEW STAGE AND PROSPECTS FOR COOPERATION BETWEEN UZBEKISTAN AND TAJIKISTAN IN THE FIELD OF CULTURE AND ARTS - Sulaymanova , Muhiba Boltaevna (Educational Research in Universal Sciences, 2023)
This article highlights the prospects for promoting cooperation between Uzbekistan and Tajikistan to a new level in the culture and art of the fraternal peoples.